Enteric infections and immunity - Paradise, Lois J; Bendinelli, Mauro; Friedman, Herman (Plenum Press, 1996)
This comprehensive reference describes the current state of knowledge on the mechanisms of action of toxins, virulence factors, and mechanisms of invasion for the major groups of enteric microorganisms. This work also features the latest studies on the effects of eukaryotic cell signaling as well as stimulation of the inflammatory response by induction and the actions of cytokines. Researchers and students in microbiology, gastroenterology, and immunobiology will appreciate this important work.
Infectious agents and pathogenesis
Keywords: Bacterial Infections and Mycoses; Inflammatory Bowel Diseases; idiopatické střevní záněty; gastroenterologie; Bacteria; střevní sliznice; bakteriální infekce a mykózy; alergologie a imunologie; Intestinal Mucosa; infekční lékařství